PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PADA JASA PEMANDUAN PT. BIAS DELTA PRATAMA - LA ODE MUHAMMAD TAUHA; NUR ELFI HUSDA (JURNAL ILMIAH MAKSITEK, 2020)
Service quality plays an important role in a company because it will affect customer satisfaction, resulting in loyalty. Serviceproviders must provide friendly, courteous and good services to provide satisfaction to consumers. PT Bias Delta Pratama isone of the Port Business Entities that has obtained a scouting permit. The population in this study was 150 people. Usingslovin sampling. Data collection techniques using questionnaires and documentation. The measurement scale used is aLikert scale. Data collected in this study were analyzed by multiple linear regression analysis with the help of SPSS (Productand Service Solution Statistics) version 21. T test results showed that service quality (X1) had a positive and significant effecton customer satisfaction (Y) with tcount of quality variables service (X1) is 2,062> 1,976 (table). Facility (X2) has a positiveand significant effect on customer satisfaction (Y) with a tcount of 5.103> 1.976 (table). F test results show that servicequality (X1) and facility (X2) variables together have a positive and significant effect on customer satisfaction (Y).